Croton guatemalensis (Euphorbiaceae) phenology at the Zoque Tropical Forest Biological Corridor - Pozo-Gómez, Dulce María; Orantes-García, Carolina; Rioja-Paradela, Tamara Mila; Moreno-Moreno, Rubén Antonio; Carrillo-Reyes, Arturo (Instituto de Ecología, A.C., 2020)
Croton guatemalensis is a threatened and multipurpose species in communities of southeastern Mexico and Central America. For the first time, its reproductive phenology and its relationship with environmental variables present in four different natural protected areas of the Zoque Tropical Forest Biological Corridor was determined. Throughout a year the flowering and fructification of the species was monitored, the local environmental variables were recorded and fruits and seeds were collected to determine, under a random design, the germination of the seeds and the growth of seedlings in the laboratory and in nursery respectively. In all cases, flowering was presented from July to April, while fructification occurred from March to September, coinciding with the months where the rains diminish considerably. In terms of seed germination, it presented a statistically significant difference between seeds from the four protected areas. The most contrasting results were presented between La Pera and Area Villa de Allende (98% ± 3.84% and 6% ± 3.84% respectively). According to the generalized linear model, soil porosity was the only variable that influenced the germination of the species (the higher the porosity, the higher the percentage of final germination, t = 2.237, P = 0.0503). Because this is the first study on the ecophysiology of C. guatemalensis in southern Mexico, the importance of it becomes relevant when providing fundamental reproductive information for the generation of strategies for conservation, restoration and forest management of the species.